Narrow-Band Imaging: Clinical Application in Gastrointestinal Endoscopy - Barbeiro,Sandra (2019)
Narrow-band imaging is an advanced imaging system that applies optic digital methods to enhance endoscopic images and improves visualization of the mucosal surface architecture and microvascular pattern. Narrow-band imaging use has been suggested to be an important adjunctive tool to white-light endoscopy to improve the detection of lesions in the digestive tract. Importantly, it also allows the distinction between benign and malignant lesions, targeting biopsies, prediction of the risk of invasive cancer, delimitation of resection margins, and identification of residual neoplasia in a scar. Thus, in expert hands it is a useful tool that enables the physician to decide on the best treatment (endoscopic or surgical) and management. Current evidence suggests that it should be used routinely for patients at increased risk for digestive neoplastic lesions and could become the standard of care in the near future, at least in referral centers. However, adequate training programs to promote the implementation of narrow-band imaging in daily clinical practice are needed. In this review, we summarize the current scientific evidence on the clinical usefulness of narrow-band imaging in the diagnosis and characterization of digestive tract lesions/cancers and describe the available classification systems.